CHALLENGE OF LEARNING ENGLISH FROM REVOLUTION AS 21st CENTURY LEARNING FOR COMMUNITIES 5.0 - Dina Purnama Sari (Universitas Muhammadiyah Kalimantan Timur, 2020)
Brown, John Seely. (2005). New Learning Environments for the 21st Century*retrieved from http://www.johnseelybrown.com/newlearning.pdf Delors, Jacques. (2013). The treasure within: Learning to know, learning to do, learning to live together and learning to be. What is the value of that treasure 15 years after its publication? Int Rev Educ 59:319–330. retrieved from http://www.oosci-mena.org/uploads/1/wysiwyg/Delors_article_review_of_education_2013.pdf Karinov. (2019). Revolusi Industri Ala Jepang: Hjuman-Centered Society. Retrieved From https://Karinov.Co.Id/Revolusi-Industri-5-Jepang/ Malik, Ranbir Singh. (2018). Educational Challenges In 21st Century And Sustainable Development. Journal of Sustainable Development Education and Research. JSDER Vol. 2, No.1. 9-20. retrieved from File:///C:/Users/User.User-PC.000/Downloads/12266-25620-1-SM.Pdf Marcellino, M. (2008). English Language Teaching In Indonesia: A Continuous Challenge In Education And Cultural Diversity. TEFLIN Journal, Volume 19, Number 1, February. 57 – 69. retrieved from http://journal.teflin.org/index.php/journal/article/viewFile/99/93 Niara, Kita. (2016). Bahasa Inggris untuk Bisnis 01 - Bagaimana Memperkenalkan Staf Perusahaan. Retrieved from https://www.youtube.com/watch?v=xz3qXl6nro4 Niara, Kita. (2016). Bahasa Inggris untuk Bisnis 02 - Memperkenalkan Tim/Staf Perusahaan Bag. 2. Retrieved from https://www.youtube.com/watch?v=8qBq7CJc_z0 Singh, Raja Roy. (1991). Education for The Twenty First Century: Asia-Pasific Perspective. Bangkok: UNESCO. retrieved from http://www.unesco.org/education/pdf/15_15.pdf